Factors related to the preparation of the working-age population to support the aging society in Buached District, Surin Province - Sampao, Sawinee; Suebsumrarn, Palakorn; Boonsang, Arun; Limpiteeprakan, Pawena (Journal of Medical and Public Health Region 4, 2024)
Preparation for an aging society is crucial for the working population, as they need to prepare themselves for the aging process's various aspects, including its impact on quality of life. The purpose of this research was to study the factors associated with the readiness of the working-age population to support an aging society in the Buachet District of Surin Province. A cross-sectional analytical study was conducted involving 330 individuals aged 40-59, selected through stratified random sampling. The research utilized a questionnaire as the primary research tool and employed descriptive statistics to analyze the collected data. Factors related to the preparedness of the working-age population to support an aging society were examined using multivariate logistic regression. The research findings were presented using adjusted odds ratios (ORadj) with 95% confidence intervals (CI) and a significance level (P-value) of less than .05. The results of the study revealed that the sample group perceived a high level of readiness to support an aging society (95.2 percent) and held a positive attitude towards preparing for it (97.0 percent). However, the preparedness to support an aging society was lacking (70.9 percent). The factors that showed statistical significance (P-value < .05) with readiness were average monthly income and recognition by the population with an average monthly income of over 3,000 baht and good recognition. Individuals in this category were 2.88 times more likely to be better prepared (ORadj = 2.88, 95% CI: 1.40-4.16) and 8.21 times more likely (ORadj = 8.21, 95% CI: 1.00-17.54) compared to those with an average monthly income of less than 3,000 baht and moderate awareness. Therefore, it is crucial to encourage the working population to have a stable income, promote vocational skills, generate income, manage their finances, develop savings habits, and create awareness among people of all ages. These efforts aim to increase awareness and enhance preparedness to support an aging society better.